2022
DOI: 10.1029/2021sw002854
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Global Ionospheric TEC Based on Deep Learning

Abstract: The accurate prediction of ionospheric Total Electron Content (TEC) is important for global navigation satellite systems (GNSS), satellite communications and other space communications applications. In this study, a prediction model of global IGS‐TEC maps are established based on testing several different long short‐term memory (LSTM) network (LSTM)‐based algorithms to explore a direction that can effectively alleviate the increasing error with prediction time. We find that a Multi‐step auxiliary algorithm bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 19 publications
4
54
0
Order By: Relevance
“…Moreover, Chen et al. (2022) used four different LSTM‐based algorithms (single‐step self‐prediction model, single‐step auxiliary prediction model, multi‐step self‐prediction model, and multi‐step auxiliary prediction [MSAP] model) to predict global IGS‐TEC maps. They found that the MSAP model can effectively alleviate the increasing error with prediction time; the MSAP model can better predict the global IGS‐TEC in the next 6 days with RMSE of 3.511 TECU, which is much smaller than 5.593 TECU of the IRI‐2016 model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chen et al. (2022) used four different LSTM‐based algorithms (single‐step self‐prediction model, single‐step auxiliary prediction model, multi‐step self‐prediction model, and multi‐step auxiliary prediction [MSAP] model) to predict global IGS‐TEC maps. They found that the MSAP model can effectively alleviate the increasing error with prediction time; the MSAP model can better predict the global IGS‐TEC in the next 6 days with RMSE of 3.511 TECU, which is much smaller than 5.593 TECU of the IRI‐2016 model.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the modified U-Net model was also compared with that of other state-of-the-art ML models. Chen et al (2022) used long short-term memory (LSTM) network-based algorithms to predict the GIMs between 2011 and 2019. They achieved an RMSE of 3.03, 3.18, and 3.51 TECU for 1-day, 2-day, and 6-day predictions, respectively.…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
“…To the best of our knowledge, all global TEC forecast models mentioned above were trained with IGS GIMs or GIMs from a specific IAAC (Cesaroni et al, 2020;Chen et al, 2022;Lee et al, 2021;L. Liu et al, , 2022J.…”
mentioning
confidence: 99%
“…Chen et al. (2022) utilized a prediction model of global IGS (International Global Navigation Satellite System Service)‐TEC (Total Electron Content [TEC]) maps that are established based on testing several different LSTM network based algorithms to predict ionospheric TEC.…”
Section: Introductionmentioning
confidence: 99%